The Perceptions of Bank Clients Toward Collection Mechanisms: A Phenomenological State of the Art Analysis - Aguilar Aguilar, Graciela; Rodríguez, Giraldo de la Caridad León (CV. Literasi Indonesia, 2025)
Bank debt collection mechanisms have evolved alongside technological advancements and the transformation of business models in the financial sector, creating new forms of interaction with clients. However, this transformation has not been free from tension, where private banking clients have increasingly been exposed to collection strategies often perceived as invasive or disproportionate. This article, which seeks to interpret the phenomenon from a phenomenological perspective, examines the perception of bank clients regarding collection mechanisms through a critical analysis, aiming to identify significant emerging categories that explain their influence on decision-making processes. The research follows a constructivist epistemological framework, adopting a qualitative approach and documentary design. Using content analysis techniques and source saturation, five key heuristics emerged: (1) client depersonalization, (2) ambivalence between effectiveness and fair treatment, (3) psycho-emotional impacts, (4) decision-making under pressure, and (5) the moralization of debt. The results allow for a re-understanding of the phenomenon from an ethical and human-centered perspective, contributing to theoretical constructs that place the client’s lived experience at the core of the analysis. The study concludes with recommendations to humanize debt collection models, strengthen the client–bank relationship, and implement policies guided by the dignity of the indebted individual.